1985
DOI: 10.1111/j.1365-3024.1985.tb00107.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum dependent cell‐mediated immune reactions to Brugia pahangi infective larvae*

Abstract: Fresh normal rat serum (fNRS) promoted adherence and cytotoxicity of albino rat neutrophils and macrophages to Brugia pahangi infective larvae (L3) in vitro. EDTA and not EGTA abolished the adherence activity suggesting the involvement of complement components via the alternate pathway. C3 molecules were detected on the surface of the parasite by immunofluorescence. fNRS depleted of complement by treatment with Zymosan A or of factor B by heating at 50 degrees C for 20 min, failed to promote cell adherence to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 6 publications
1
24
0
Order By: Relevance
“…ADCC is one of the principal immunological mechanisms working behind the dis-appearance of circulating filarial parasites and their clearance [15,16,23]. Here in, we observed that the sera from mastomys immunized with rWbGST promoted adherence of peritoneal exudate cells to L 3 larvae and induced significant killing of parasite (71.55 % of cytotoxicity against L3).…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…ADCC is one of the principal immunological mechanisms working behind the dis-appearance of circulating filarial parasites and their clearance [15,16,23]. Here in, we observed that the sera from mastomys immunized with rWbGST promoted adherence of peritoneal exudate cells to L 3 larvae and induced significant killing of parasite (71.55 % of cytotoxicity against L3).…”
Section: Discussionsupporting
confidence: 56%
“…The cytotoxic effect of anti-rWbGST antibodies against B. malayi L 3 larvae was determined by in vitro cytotoxicity assay by the method described previously [7,15,16]. Pooled sera samples from immunized mastomys before and after depletion of anti-WbGST antibodies were used in this assay.…”
Section: In Vitro Antibody Dependent Cellular Cytotoxicity (Adcc) Assaymentioning
confidence: 99%
“…We reasoned that the defect in these mice, in contrast to T cell-deficient mice, was not in cell recruitment but at a later stage in host defense, perhaps in adherence of leukocytes to larvae to initiate granuloma formation. To determine whether IgM played a role in adherence of PECs to worms, we used an adaptation of an in vitro assay previously described by Chandrashekar et al (23). We tested the adherence of peritoneal cells to Brugia L3 from naive or primed wt and secIgM Ϫ/Ϫ mice in the presence of either naive or primed sera.…”
Section: Igm Is Essential For Cell Adherence To Brugia L3mentioning
confidence: 99%
“…22,23 ADCC is one of the principal immunological mechanisms working behind the dis-appearance of circulating filarial parasites and their clearance. 15,16,24 Here in, we observed that the sera from mastomys immunized with rWbL 2 promoted adherence of peritoneal exudate cells to L 3 larvae and induced significant killing of parasite (53.89% of cytotoxicity against L 3 ). Whereas, depletion of these antibodies from the sera of immunized mastomys reverted the killing activity of parasite.…”
Section: Effect On the Splenocytes Proliferation And Cytokine Analysismentioning
confidence: 74%
“…7,15,16 Pooled sera samples from immunized mastomys before and after depletion of anti-WbL 2 antibodies were used in this assay. The ADCC assay was performed by adding about 20 L 3 larvae of B. malayi to a suspension of peritoneal exudates cells (PEC; 2 x 10 5 cells / well in 100 μl of RPMI medium) collected from normal mastomys.…”
Section: In Vitro Antibody Dependent Cellular Cytotoxicity Assay (Adcc)mentioning
confidence: 99%